El anticapitalismo y sus aproximaciones al trabajo social brasileño: anunciando algunas controversias y concepciones - Kelly Rodrigues Melatti; Terezinha de Fátima Rodrigues; Maria Carmelita Yazbek (Eleuthera)
This article reflects some theoretical controversies about the concepts that involve anti-capitalism in its multiple forms of expression and ideopolitical meanings present in critical social theory and presents, in an approximate way, the particularity of brazilian social work in the context of anti-capitalist struggles. This study is based on theoretical reflections from authors who problematize anticapitalism in the theoretical-critical dimension. Its central question is: How is brazilian social work linked to anticapitalist struggles? The presence of anticapitalism in brazilian social service is a reflection of its professional project, which is aimed at achieving human emancipation. This presence is expressed through the organic linkages with social movements and struggles in a highly unequal brazilian society, marked by late capitalism, dependence, subordination, and reconfigured forms of colonial slavery in the shape of racist and patriarchal practices. This is the fertile ground of anti-capitalist struggles, and brazilian social work have not shied away from this ethical and political insertion, even though tensions and contradictions permeate it.